Impact Melt Facies in the Moon's Crisium Basin: Identifying, Characterizing, and Future Radiogenic Dating. Issue 1 (5th January 2020) - Runyon, K. D.; Moriarty, D. P.; Denevi, B. W.; Greenhagen, B. T.; Morgan, G.; Young, K. E.; Cohen, B. A.; van der Bogert, C. H.; Hiesinger, H.; Jozwiak, L. M.
Abstract: Both Earth and the Moon share a common history regarding the epoch of large basin formation, though only the lunar geologic record preserves any appreciable record of this Late Heavy Bombardment. The emergence of Earth's first life is approximately contemporaneous with the Late Heavy Bombardment; understanding the latter informs the environmental conditions of the former, which are likely necessary to constrain the mechanisms of abiogenesis. While the relative formation time of most of the Moon's large basins is known, the absolute timing is not. The timing of Crisium Basin's formation is one of many important events that must be constrained and would require identifying and dating impact melt formed in the Crisium event. To inform a future lunar sample dating mission, we thus characterized possible outcrops of impact melt. We determined that several mare lava‐embayed kipukas could contain impact melt, though the rim and central peaks of the partially lava‐flooded Yerkes Crater likely contain the most pure and intact Crisium impact melt. It is here where future robotic and/or human missions could confidently add a key missing piece to the puzzle of the combined issues of early Earth‐Moon bombardment and the emergence of life. Plain Language Summary: How could life get started on Earth nearly four billion years ago if our planet was constantly being impacted by asteroids and comets? While we do not yet know, we are starting to piece together parts of the answer. Earth's largest impact basins are long gone because of our planet's active geology, life, and flowing water. But the Moon's big craters are well preserved. The formation of those large basins melted lots of rocks, which then cooled; by collecting those rocks on future missions and figuring out how old they are, we can determine the timing of when large basins formed on the Moon and, by extension, on Earth. Crisium basin is one of those large basins that we need to get the age for. Most of the rock that was melted from this impact and then cooled is buried by much younger lava flows, but we believe that some of it was brought up when the crater Yerkes formed on top of Crisium. The central mountain of Yerkes Crater is where we believe future robots and/or astronauts should go to collect once‐molten rock and figure out how old it and the basin are. Key Points: Relatively pure impact melt from Crisium Basin is exposed in the central peaks of Yerkes Crater Diluted Crisium impact melt may be exposed in some previously identified kipukas in Crisium Radiogenic dating of impact melt exposed in Yerkes' central peak during a future mission would yield the age of the Crisium impact event